Neuropsicologia do esporte : funções executivas, inteligência e performance de campo em adolescentes da categoria de base do futebol - Machado, Priscila de Oliveira (2021)
Clinical, cognitive and developmental neuropsychology are the most traditional approaches of this neuroscience. The incipient sports neuropsychology is still closely related to an injury paradigm, mainly brain concussions related to sports practice. Although the literature already associates executive functions (EF) to motor and intellectual ability, greater theoretical-empirical investment in sports neuropsychology is needed, especially in the analysis of developmental aspects within sports practice. In the context of soccer, there is no consensus on which cognitive domains have a stronger association with soccer performance. So, this Master's degree dissertation aims to verify the associations between levels of EF processing (working memory; cognitive flexibility; and inhibitory control), intelligence and soccer performance among soccer players. The theoretical study 1 is a review of publications that evaluated EF in soccer players. The empirical, cross-sectional study 2 analyzed the data of 67 male U-14 soccer players from two soccer clubs (one elite club and one sub-elite club) in Southern Brazil. More specifically, the objectives of study 2 were as follows: 1) to compare the elite club’s players with the sub-elite club’s players in relation to EF and intelligence scores; 2) to compare players of different soccer positions in relation to EF and intelligence scores. The athletes had been previously evaluated in a university extension project in 2018 and 2019. The assessment included a clinical instrument answered by the coaches (SNAP-IV ADHD scale) and an extensive individual neuropsychological assessment with the players, including instruments that assess intelligence and the three core EF (inhibitory control; working memory; and cognitive flexibility), such as the Unconstrained Verbal Fluency Task, the WASI Scale, the Digit Backwards Subtest (WISC-IV), the Hayling Sentence Completion Test, the Five Digit Test, the Oral Word Span in Sentences Subtest (NEUPSILIN), the Trail Making Test, the Odd One Out Test and the Go/No-go App Test. The main results were that 1) there was no difference between elite and sub-elite clubs’ players regarding intelligence scores, but the elite club’s players performed better in tests of the three core EF (more consistently in inhibitory control tasks); 2) defenders scored better than midfielders and forwards in two subscores of the Hayling - part B test, which assesses mainly inhibitory control. Both the literature review in study 1 and the results of study 2 reinforce that there is an association between EF and soccer performance. With a broader perspective, the neuropsychological paradigms and the interventions that assess and stimulate EF may contribute to the training of young athletes and also to the cognitive-motor development of school-age students. Neuropsychology can be a useful tool to enrich the professional training of physical educators and to qualify the planning of beneficial practices both in a sports context and in a school environment.